Newborn and child health national and provincial clinical practice guidelines in South Africa, Nigeria and Malawi: a scoping review - Mashudu Mthethwa; Nyanyiwe Masingi Mbeye; Emmanuel Effa; Dachi Arikpo; Ntombifuthi Blose; Amanda Brand; Moriam Chibuzor; Roselyn Chipojola; Solange Durao; Ekpereonne Esu; Idriss Ibrahim Kallon; Gertrude Kunje; et al. (BMC, 2024)
Abstract Background Low and middle-income countries remain disproportionately affected by high rates of child mortality. Clinical practice guidelines are essential clinical tools supporting implementation of effective, safe, and cost-effective healthcare. High-quality evidence-based guidelines play a key role in improving clinical management to impact child mortality. We aimed to identify and assess the quality of guidelines for newborn and child health published in South Africa, Nigeria and Malawi in the last 5 years (2017-2022). Methods We searched relevant websites (June-July 2022), for publicly available national and subnational de novo or adapted guidelines, addressing newborn and child health in the three countries. Pairs of reviewers independently extracted information from eligible guidelines (scope, topic, target population and users, responsible developers, stakeholder consultation process, adaptation description, assessment of evidence certainty). We appraised guideline quality using the Appraisal of Guidelines for Research & Evaluation (AGREE II) instrument. Results We identified 40-guidelines from the three countries. Of these, 8/40 reported being adopted from a parent guideline. More guidelines (n = 19) provided guidance on communicable diseases than on non-communicable diseases (n = 8). Guidelines were most often developed by national health ministries (n = 30) and professional societies (n = 14). Eighteen guidelines reported on stakeholder consultation; with Nigeria (10/11) and Malawi (3/6) faring better than South Africa (5/23) in reporting this activity. The Grading of Recommendations, Assessment, Development, and Evaluations (GRADE) approach was used in 1/7 guidelines that reported assessing certainty of evidence. Overall guidelines scored well on two AGREE II domains: scope and purpose median (IQR) score 68% (IQR 47-83), and clarity of presentation 81% (67-94). Domains critical for ensuring credible guidance scored below 20%: rigour of development 11% (4-32) and editorial independence 6% (0-27). Conclusion National ministries and professional societies drive guideline activities in Malawi, Nigeria and South Arica. However, the methods and reporting do not adhere to global standards. We found low AGREE II scores for rigour of guideline development and editorial independence and limited use of GRADE or adaptation methods. This undermines the credibility of available guidelines to support evidence-informed care. Our findings highlight the importance of ongoing efforts to strengthen partnerships, capacity, and support for guideline development.